2016
DOI: 10.1080/13548506.2016.1210176
|View full text |Cite
|
Sign up to set email alerts
|

Hidden reality: sexual sphere in brain tumor patients

Abstract: Most reports emphasize that tumors and their treatments affect sexual function. To date, no studies have focused on sexual functioning in patients with brain tumors. Our study's objective is to describe the sexual sphere of patients with brain tumors and examine the possible differences between patients who reported sexual dysfunctions and those who did not with respect to their psychological and functional status. We tested 46 patients with brain tumors. We used an ad hoc questionnaire to assess patients' sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
12
2
Order By: Relevance
“…We identified a total of three [ 10 , 24 , 25 ] studies, which address SD incidence and/or associations between SD and QoL ( Figure 1 ). Handsearching of articles revealed 60 additional articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified a total of three [ 10 , 24 , 25 ] studies, which address SD incidence and/or associations between SD and QoL ( Figure 1 ). Handsearching of articles revealed 60 additional articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ...…”
Section: Resultsmentioning
confidence: 99%
“…Using an ad hoc interview, Finocchiaro et al [ 24 ] investigated the sexual activity of 46 patients with brain tumors, including 21 LGG patients. They observed that 58% of brain tumor patients reported SD at the time of evaluation and 34% reported that the onset of disturbance only occurs after diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that surveyed colorectal cancer survivors found that there is a need for the development of interventions for this patient population to manage sexual dysfunction [16]. In the field of central nerve system tumors, Finocchiaro et al is one of the few studies that focused on sexual dysfunction in patients suffering from brain tumors [7]. They surveyed patients with brain tumors and showed that the majority (84.8%) did not receive or request information regarding sexual health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, sexual health and functioning are seen as one of the many determinants of QoL. Brain tumor patients that reported more sexual problems also reported more anxiety and were more likely to have an impaired self-reported QoL [7,8]. Following brain tumor onset, patients develop symptoms such as disorder of sexual desire, disorders of orgasm, arousal disorders and in general more anxiety and depression [7,8].…”
Section: Introductionmentioning
confidence: 99%